Vlaanderen zendt zijn zonen uit - Olbrechts, Frans M., 1899-1958; Davidsfonds; Van Noten, Jan (Leuven : Davidsfonds, 1942)
Dromen, mythen en legenden - Willem van Rubroek naar Mongolië - Joos van Ghistel - Pieter van Gent - Niklaas Cleynaerts -Ogier van Busbeek - Emanuel de Aranda - Ferdinand Verbiest - Joris van Geel - Pieter Fardé
Keywords: Flemings